PERSPECTIVE OF RELIGIOUS JUSTICE IN THE FORMULATION OF PENAL REFORM - Reski Anwar; Faisal Faisal; Rio Amanda Agustin (Universitas Lampung, 2021)
The perspective of justice from law enforcement is only on the law’s guidance, not based on God’s guidance that prioritizes substantive justice. The idea of religious justice contained in the renewal of criminal law there is Article 53 paragraph (2), with the provision reads in considering the establishment of law and justice as referred to in paragraph (1) there is a conflict that can not be met, the judge must prioritize justice. The recommendations are stated because the explanation of Article 53 paragraph (2) says that justice and legal certainty are two legal objectives that are often not in line with each other and difficult to avoid in legal practice. A rule of law that meets more legal certainty demands, the more likely aspects of justice are urged. Metode research used in this study is normative research, namely research on library materials that are essential data that is classified as secondary data that rests on data collection tools similar to literature studies or document studies. The results showed that if in the application of concrete events, justice and legal certainty are mutually urgent, then the judge, as far as possible, prioritizes justice over legal certainty. Religious Justice that exists in the value of Pancasila formulated into the renewal of criminal law justice contains a demand that people treat others following their rights and obligations. The treatment is not indiscriminate or compassionate; instead, everyone is treated equally under their rights and responsibilities.